Critical issues in cognitive behavioural therapy (CBT) with gender and sexual minorities (GSMs). (12th January 2022) - Carvalho, Sérgio A.; Castilho, Paula; Seabra, Daniel; Salvador, Céu; Rijo, Daniel; Carona, Carlos
Abstract: In a cisheteronormative culture, gender and sexual minorities (GSMs) may experience additional challenges that get in the way of a meaningful life. It is crucial that clinicians are mindful of these challenges and cognizant about the specificities of clinical work with GSMs. This article points out how societal structure interferes with mental health, and clarifies what clinicians must take into account when using affirmative cognitive behavioural therapy (CBT) interventions. Knowledge of up-to-date terminology and use of affirmative language are the first steps that contribute to clients' experience of respect, which is paramount for the development of a good therapeutic relationship. Considering a conceptual framework of minority stress to understand vulnerability in GSM, specificities in formulation and key psychological processes are discussed. Moreover, guidelines and practical tools for intervention are presented within a CBT approach. Some reflections on therapists' own personal biases are encouraged, in order to increase the efficacy of interventions. Key learning aims: After reading this article you will be able to: (1) Recognize the uniqueness of gender and sexual minorities (GSM) stressors in broad and specific contexts, and their impact on mental health. (2) Identify the underlying key processes and specificities in therapeutic work with GSMs, from a CBT perspective. (3) Recognize the importance of a culturally sensitive approach in affirmative CBT interventions.